2022
DOI: 10.1007/s40145-022-0621-3
|View full text |Cite
|
Sign up to set email alerts
|

Construction and performance of CdS/MoO2@Mo2C-MXene photocatalyst for H2 production

Abstract: Nowadays, photocatalytic technologies are regarded as promising strategies to solve energy problems, and various photocatalysts have been synthesized and explored. In this paper, a novel CdS/MoO2@Mo2C-MXene photocatalyst for H2 production was constructed by a two-step hydrothermal method, where MoO2@Mo2C-MXene acted as a binary co-catalyst. In the first hydrothermal step, MoO2 crystals with an egged shape grew on the surface of two-dimensional (2D) Mo2C MXene via an oxidation process in HCl aqueous solution. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…Guo and coworkers reported that MoB MBene exhibits great catalytic activity for hydrogen evolution reactions, indicating its promising application as electrocatalysts for hydrogen evolution [28]. In addition, the MoB MBene has a potential application in H2 production, similar to the Mo2C MXene which acts as a visible-light photocatalyst for H2 production partially due to the more activity of Mo element [29,30]. Mo2AlB2 is a MAB phase and has an orthorhombic crystal structure containing stacked M-B blocks interleaved with a monolayer of Al.…”
Section: Journal Of Advanced Ceramicsmentioning
confidence: 99%
“…Guo and coworkers reported that MoB MBene exhibits great catalytic activity for hydrogen evolution reactions, indicating its promising application as electrocatalysts for hydrogen evolution [28]. In addition, the MoB MBene has a potential application in H2 production, similar to the Mo2C MXene which acts as a visible-light photocatalyst for H2 production partially due to the more activity of Mo element [29,30]. Mo2AlB2 is a MAB phase and has an orthorhombic crystal structure containing stacked M-B blocks interleaved with a monolayer of Al.…”
Section: Journal Of Advanced Ceramicsmentioning
confidence: 99%
“…The spectrum of Mo 3d was deconvoluted into six peaks (Figure b), corresponding to the Mo 4+ 3d 5/2 and 3d 3/2 , Mo 5+ 3d 5/2 and 3d 3/2 , and Mo 6+ 3d 5/2 and 3d 3/2 (229.9 and 232.5, 231.3 and 234.7, and 233.2 and 236 eV, respectively). , The Mo 4+ is originated from MoO 2 . The appearance of Mo 5+ and Mo 6+ is attributed to inevitable oxidation that occurred at the surface of MoO 2 , but the main component is still MoO 2 . , …”
Section: Resultsmentioning
confidence: 99%
“…The appearance of Mo 5+ and Mo 6+ is attributed to inevitable oxidation that occurred at the surface of MoO 2 , but the main component is still MoO 2 . 37,38 The deconvolution of the O 1s spectrum (Figure 3c) revealed the bonds of O−Mo (530.6 eV) in MoO 2 , and O−H and O−Si (531.4 and 532.3 eV, respectively) from SiO 2 in MoSi 2 . 20,39 The Mo 3d and O 1s XPS spectra of the other MoSi 2 -based electrodes are illustrated in Figure S5, Supporting Information.…”
Section: ■ Experimental Partmentioning
confidence: 99%
“…This indicates the successful transformation from Mo 2 Ga 2 C to Mo 2 C MXene. 19,20,24,32,33 All the Mo The XPS spectra of pure CdS, CM-Li, and Mo 2 C−Li are shown in Figure 2. From the full-scale XPS spectrum in Figure 2a, the elements of Cd, S, O, and Mo were detected in the typical CM-Li.…”
Section: ■ Results and Discussionmentioning
confidence: 99%